Nitric Oxide and Small and Intermediate Calcium-Activated Potassium Channels Mediate the Vasodilation Induced by Apigenin in the Resistance Vessels of Hypertensive Rats - Lislaine Maria Klider; Maria Luiza Fidelis da Silva; Gustavo Ratti da Silva; João Ricardo Cray da Costa; Marcia Alessandra Arantes Marques; Emerson Luiz Botelho Lourenço; Francislaine Aparecida dos Reis Lívero; Jane Manfron; Arquimedes Gasparotto Junior (Molecules, 2024)
Background: Apigenin (4′,5,7-trihydroxyflavone), a flavonoid with potential cardiovascular benefits, has unclear mechanisms of action. This study investigates its effects on vascular function in Spontaneously Hypertensive Rats (SHRs). Methods: Mesenteric vascular beds (MVBs) were isolated from SHRs and perfused with increasing doses of apigenin after pre-contraction with phenylephrine. To explore the mechanisms, different MVBs were pre-perfused with antagonists and inhibitors, including indomethacin, L-NAME, and potassium channel blockers (tetraethylammonium, a non-specific potassium channel blocker; glibenclamide, an ATP-sensitive potassium channel blocker; 4-aminopyridine, a voltage-gated potassium channel blocker; charybdotoxin a selective intermediate-conductance calcium-activated potassium channel blocker; and apamin, a selective small-conductance calcium-activated potassium channel blocker). Results: Apigenin induced a dose-dependent reduction in perfusion pressure in MVBs with intact endothelium, an effect abolished by endothelium removal. L-NAME reduced apigenin-induced vasodilation by approximately 40%. The vasodilatory effect was blocked by potassium chloride and tetraethylammonium. The inhibition of small and intermediate calcium-activated potassium channels with charybdotoxin and apamin reduced apigenin-induced vasodilation by 50%, and a combination of these blockers with L-NAME completely inhibited the effect. Conclusions: Apigenin promotes vasodilation in resistance arteries through endothelial nitric oxide and calcium-activated potassium channels. These findings suggest that apigenin could have therapeutic potential in cardiovascular disease, warranting further clinical research.